Dynamics of ionic liquids in the presence of polymer-grafted nanoparticles. Issue 42 (1st August 2019) - Liu, Siqi; Liedel, Clemens; Tarakina, Nadezda V.; Osti, Naresh C.; Akcora, Pinar
Abstract : Long-range diffusion coefficient ( D slow ) of HMIM + cations is higher than that of zwitterionic liquid (BMIM-BH3 ) when mixed with the polymer. Abstract : We incorporated polymer-grafted nanoparticles into ionic and zwitterionic liquids to explore the solvation and confinement effects on their heterogeneous dynamics using quasi-elastic neutron scattering (QENS). 1-Hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (HMIM-TFSI) mixed with deuterated poly(methyl methacrylate) (d-PMMA)-grafted nanoparticles is studied to unravel how dynamic coupling between PMMA and HMIM-TFSI influence the fast and slow diffusion characteristics of the HMIM + cations. The zwitterionic liquid, 1-butyl-3-methyl imidazole-2-ylidene borane (BMIM-BH3 ) is critically selected and mixed with PMMA-grafted nanoparticles for comparison in this work as its ions do not self-dissociate and it does not couple with PMMA through ion-dipole interactions as HMIM-TFSI does. We find that long-range unrestricted diffusion of HMIM + cations is higher in well-dispersed particles than in aggregated particle systems, whereas the localized diffusion of HMIM + is measured to be higher in close-packed particles. Translational diffusion dynamics of BMIM-BH3 is not influenced by any particle structures suggesting that zwitterions do not interact with PMMA. This difference between two ionic liquid types enables us to decouple polymer effects from the diffusion of ionic liquids, which is integral to understand the ionic transport mechanism in ionic liquids confined in polymer-grafted nanoparticle electrolytes.